Islamic Boarding School Paradigm: As a Religious Education Institution and Strengthening Student Character - Susanto, Susanto; Ritonga, Apri Wardana; Ayu Desrani (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
In Era Society 5.0, Indonesia is faced with the swift currents of globalization, a process of order owned by the global community that knows no boundaries. This is also happening in the field of education in Indonesia which is the cause of the nation's downturn on the grounds that our education does not produce good human resources. National character is something that is important to advance a nation. To overcome this, changes are needed in the learning of the Islamic boarding school program for students' religious learning. Therefore, the purpose of this study is to describe the application of character education in religious learning through a short Islamic boarding school program. The method used is descriptive qualitative by collecting data through observation and interviews. These observations and interviews were conducted with teachers and students at MAN 3 Palembang. Data analysis uses the theory of Milles and Huberman, namely data reduction, data presentation, and verification. The results of this study were: 1) At MAN 3 Palembang, they implemented religious learning through several activities, namely book study, speech, al-Barzani, reciting al-Qur’an, reading Yasin, evening tutoring, and performing arts; 2) The characters that can be produced from these activities are religious, responsible, disciplined, confident, creative, communicative, curious, polite, courteous, patient, sincere, humble, independent, honest, respectful, creative, and innovative. The findings of this study are that the flash Islamic boarding school program implemented at MAN 3 Palembang can build student' character to become better individuals.